2017
DOI: 10.1016/j.bbadis.2017.07.034
|View full text |Cite
|
Sign up to set email alerts
|

MiR-485-5p modulates mitochondrial fission through targeting mitochondrial anchored protein ligase in cardiac hypertrophy

Abstract: The pathogenesis of cardiac hypertrophy is tightly associated with mitochondrial dysfunction. Disequilibrium of mitochondrial dynamic is one of the main drivers in the pathological processes during development of various cardiac diseases. However, the effect of mitochondrial dynamics on cardiac hypertrophy remains largely unclear. MicroRNAs (miRNAs) are small noncoding RNAs that can switch off expression of many genes. Mitochondrial anchored protein ligase (MAPL) is a small ubiquitin-like modifier (SUMO) E3 li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 47 publications
5
42
0
Order By: Relevance
“…However, this balance is disrupted under stress conditions, resulting in apoptosis. 31 In the current study, we found that the mi- injury. Furthermore, these protective effects were partially reversed by ZnPP, a haemin inhibitor.…”
Section: Discussionsupporting
confidence: 52%
“…However, this balance is disrupted under stress conditions, resulting in apoptosis. 31 In the current study, we found that the mi- injury. Furthermore, these protective effects were partially reversed by ZnPP, a haemin inhibitor.…”
Section: Discussionsupporting
confidence: 52%
“…Thus, it provides new evidences to explore the functions of miRNAs in modulating mitochondrial function. For instance, miR‐106a accelerates cardiac hypertrophy via restraining mitofusin 2, miR‐497 and miR‐485‐5p attenuate cardiac hypertrophy by targeting Sirt4 and MAPL, respectively . In present study, we found that miRNA‐miR‐376b‐3p negatively regulate mitochondrial fission in cardiac hypertrophic NRVCs by targeting MFF.…”
Section: Discussionsupporting
confidence: 55%
“…For instance, miR-106a accelerates cardiac hypertrophy via restraining mitofusin 2, 30 miR-497 and miR-485-5p attenuate cardiac hypertrophy by targeting Sirt4 and MAPL, respectively. 26,31 In present study, we found that miRNA-miR-376b-3p negatively regulate mitochondrial fission in cardiac hypertrophic NRVCs by targeting MFF. miR-376b plays major roles in regulating of various biology activities including cancer, 32,33 liver regeneration, 34 angiogenesis 35 and cardioprotection.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, miR-30 has been reported to antagonize apoptosis of cardiac cells through negatively regulating Drp1, an initiator of mitochondrial fission, Bcl-2, and Bnip3L/Nix, leading to apoptosis [55,68]. MiR-485-5p directly downregulated mitochondrial anchored protein ligase, an important contributor in the mitochondrial fission process, and upregulated mitochondrial fusion protein 2 (Mfn2) in primary hypertrophic cardiomyocytes [69]. In vivo, miR-485-5p agomir suppressed cardiac hypertrophy in mice [69].…”
Section: Cardiac Hypertrophymentioning
confidence: 99%
“…MiR-485-5p directly downregulated mitochondrial anchored protein ligase, an important contributor in the mitochondrial fission process, and upregulated mitochondrial fusion protein 2 (Mfn2) in primary hypertrophic cardiomyocytes [69]. In vivo, miR-485-5p agomir suppressed cardiac hypertrophy in mice [69]. Thus, mitomiRs may be potential markers in cardiac hypertrophy and may negatively or positively regulate the progression of pathological cardiac remodeling through modulation of mitochondrial fusion-fission and function.…”
Section: Cardiac Hypertrophymentioning
confidence: 99%